Symposium: Developments in Afghanistan: Implications for Pakistan and the Region - Ayaz Wazir; Rustam Shah Mohmand; Imtiaz Gul; Babar Shah; Asad Durrani (Policy Perspectives, 2015)
Last few months have seen some significant developments in Afghanistan including, but not limited to, the presidential elections and the formation of Ghani-Abdullah national government and subsequent signing of the pending Bilateral Security Agreement (BSA) with the US. These developments will undoubtedly play an important part in shaping the internal and external dynamics of the country in years to come. It is also an established fact that any development, small or big, in Afghanistan has a bearing of one sort or the other on Pakistan as well. It was in this background that Policy Perspectives sought the analysis of selected but key Pakistani opinion makers, representing various sections of society, as to what the developments taking place across the Durand line will mean for Pakistan in addition to their overall impact upon and linkages with the regional situation. This symposium is a product of the responses thus generated over past few months' period.